Participação social em saúde no Brasil: o campo da saúde mental e suas instituições participativas/ Social participation in health in Brazil: the mental health area and participative institutions - Marazina, Isabel V. (Cadernos Brasileiros de Saúde Mental/Brazilian Journal of Mental Health, 2012)
O artigo pretende refletir sobre o estado atual da participação social no campo da saúde mental púbica brasileira. Traça um esboço histórico das instituições criadas pelo Estado a partir da legislação do Sistema Único de Saúde (SUS) e tenta dar um panorama das mesmas, assim como dos diferentes segmentos da sociedade que inteiram a rede de participação. Também assinala alguns impasses e desafios que precisam ser desdobrados para efetivar uma participação social como instrumento eficaz da construção de cidadania. ABSTRACT The article aims to reflect about the current state of social participation in Brazilian public mental health. Traces a historical outline of institutions created by the State after Unified Health System (SUS) legislation and tries to give an overview of them, as well as the different segments of society’s network participation. It also points out some difficulties and challenges that need to be deployed to effect social participation as an effective instrument of building citizenship. KEYWORDS: Mental Health; Social Participation Network; Participative Institutions.